1997
DOI: 10.1029/97jb00682
|View full text |Cite
|
Sign up to set email alerts
|

The elastic constants of San Carlos olivine to 17 GPa

Abstract: In the order (c 11, c12, c13, c22, c23, c33, c44, c55, c66 ) the 1 bar intercepts (gigapascal units) are (320.5, 68.1, 71.6, 196.5, 76.8, 233.5, 64.0, 77.0, 78.7). The first derivatives are (6.54, 3.86, 3.57, 5.38, 3.37, 5.51, 1.67, 1.81, 1.93

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
238
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(258 citation statements)
references
References 24 publications
17
238
1
2
Order By: Relevance
“…The first order derivatives are in good agreement between these two studies. The anisotropy of the olivine single crystal increases slightly with temperature (+2%) using the data of Issak (1992) and reduces slightly with increasing pressure using the data of Abramson et al (1997). One would expect the single crystal anisotropy to be nearly constant along a geotherm.…”
Section: Upper Mantlementioning
confidence: 99%
See 1 more Smart Citation
“…The first order derivatives are in good agreement between these two studies. The anisotropy of the olivine single crystal increases slightly with temperature (+2%) using the data of Issak (1992) and reduces slightly with increasing pressure using the data of Abramson et al (1997). One would expect the single crystal anisotropy to be nearly constant along a geotherm.…”
Section: Upper Mantlementioning
confidence: 99%
“…The first and second order pressure derivatives for olivine were first determined to 3 GPa by Webb (1989). However, a more recent determination to 17 GPa by Abramson et al (1997) has shown that the second order derivative is only necessary for elastic stiffness modulus C 55 . The first order derivatives are in good agreement between these two studies.…”
Section: Upper Mantlementioning
confidence: 99%
“…ρ 0 =density at room pressure (P 0 ) and temperature (T 0 ). K = bulk modulus in [GPa]: ol = 126.3 (Abramson et al, 1997); opx = 115.5 (Chai et al, 1997); cpx = 113.0 (Levien et al, 1979). K′ = bulk modulus pressure derivatives: ol = 4.28; opx = 7.82; cpx = 4.80; same authors.…”
Section: Lpo Measurement and Representationmentioning
confidence: 99%
“…C ij (P 0 ,T 0 ) = elastic constants in [GPa] at room pressure and temperature for ol (Abramson et al, 1997), opx (Chai et al, 1997) and cpx (Collins and Brown, 1998). dC ij /dP = first order pressure derivatives (nondimensional) for ol (Abramson et al, 1997), opx (Frisillo and Barsch, 1972 ⁎⁎ ) and cpx (Matsui and Busing, 1984 ⁎⁎⁎ (Isaak, 1992), opx (Chai et al, 1997) and cpx (Frisillo and Barsch, 1972 ⁎⁎⁎⁎ ).…”
Section: Lpo Measurement and Representationmentioning
confidence: 99%
“…The elastic constants used in our calculations are those of Abramson et al [1997] for olivine, Chai et al [1997] for enstatite, and Collins and Brown [1998] for diopside; we also used the Voigt Reuss Hill averaging scheme [Mainprice et al, 2000].…”
Section: Rock Seismic Propertiesmentioning
confidence: 99%